On Theories of Acceleration and Growth - Ferguson, C. E. (Quarterly Journal of Economics, 1960)
I. Introduction, 79. — II. Expectations and conventional models of growth, 82. — III. A linear, variable accelerator, 87. — IV. Simple models of growth with variable accelerator, 90. — V. Conclusions, 92. — VI. Mathematical analysis, 95.